Association of Src with Nottingham prognostic index in breast cancer: Implications for breast cancer prognostication - Primariadewi Rustamadji; Elvan Wiyarta (Wolters Kluwer Medknow Publications, 2024)
Background: Breast cancer affects one out of every eight women worldwide. Although the Nottingham Prognostic Index (NPI) is an important tool for forecasting, its accuracy remains a matter of contention. The Src protein, which has been linked to cancer proliferation and metastasis, may provide improved prognostic information. Aim: The aim of the study was to investigate the relationship between Src expression levels and the NPI in breast cancer patients. Methods: From January 2019 to December 2022, breast cancer samples were collected retrospectively. Immunohistochemistry was used to quantify Src expression, followed by digital image analysis using ImageJ software. To assure consistency, expression levels were standardized to a control protein. The samples were then stratified according to their NPI scores, and t-test was used to determine the relationship between Src expression and NPI. P <0.05 was considered statistically significant. Results: Src expression demonstrated a wide range across the 60 samples analyzed. Although there were no significant associations between Src expression and age, tumor size, or lymphovascular invasion, there was a significant correlation between the NPI and Src expression (P = 0.046). Conclusion: Increased Src expression frequently indicated a worse prognosis. Despite the absence of significant correlations with conventional factors, the study discovered a crucial relationship between NPI and Src expression.